The Clustering Analysis of Time Properties in Patients With Cerebral Small Vessel Disease: A Dynamic Connectivity Study - Yin, Wenwen; Zhou, Xia; Li, Chenchen; You, Mengzhe; Wan, Ke; Zhang, Wei; Zhu, Wenhao; Li, Mingxu; Zhu, Xiaoqun; Qian, Yinfeng; Sun, Zhongwu (Frontiers in Neurology, 2022)
Purpose: This study aimed to investigate the dynamic functional connectivity (DFC) pattern in cerebral small vessel disease(CSVD) and explore the relationships between DFC properties and cognitive impairment in CSVD. Methods: Functional data were collected from 67 CSVD patients, including 35 patients with subcortical vascular cognitive impairment (SVCI) and 32 cognitively unimpaired (CU) patients, as well as 35 healthy controls (HCs). The DFC properties were estimated by k-means clustering analysis. DFC strength analysis was used to explore the regional functional alterations between CSVD patients and HCs. The correlations between cognition and DFC parameters were also calculated. Results: The DFC analysis showed three distinct connectivity states (state I: sparsely connected, state II: strongly connected, state III: intermediate pattern). Compared with HCs, CSVD patients exhibited an increased proportion and dwelled longer in state I while opposite in state II. CSVD subgroup analyses showed that state I frequently occurred and dwelled longer in SVCI compared with CSVD-CU. Also, decreased internetwork and intranetwork functional activity in the frontal lobe, parietal lobe and occipital lobe was obvious in CSVD. Furthermore, the fractional windows and mean dwell time in state I were negatively correlated with cognition in CSVD but were opposite those in state II. Conclusion: Patients with CSVD account for a higher proportion and dwell longer in the sparsely connected state, while the opposite is true for patients in the strongly connected state, which is more prominent in SVCI. Changes in the DFC are associated with altered cognition in CSVD. Our study provides a better explanation of the potential mechanism of CSVD and the associated cognitive impairment from the perspective of DFC.